Managing irrigation - Uphoff, Norman; Ramamurthy, Priti; Steiner, Roy (New Delhi, 1991)
In conclusion, the authors present three frameworks socio-technical analysis, institution building and institutional development for improving the perfor mance of irrigation bureaucracies.
Keywords: Public administration